Helicobacter pylori, Induced Gastric Cells Apoptosis - Putut Bayupurnama (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2004)
Gastric epithelial cells apoptosis induced by Helicobacter pylori depends on microbial and host factors. Apoptosis on mitochondrial level by Bcl2 family protein is the main pathway for Helicobacter pylori induced gastric epithelial cells apoptosis, though there are roles for apoptosis through Fas receptors or TNF. Imbalance between proliferation and apoptosis gastric epithelial cells determines the risk for neoplastic transformation. Increase of gastric epithelial cells apoptosis seems to have an obligation for initiating secondary hyperproliferative response. If altruistic cellular death fails to oppose this process, uncontrollable cellular growth leading to neoplastic transformation will occur. Keywords: Helicobacter pylori, gastric cells, apoptosis